Analisis Determinan Ekspor Sulawesi Utara Ke Negara Uni Eropa Periode 2017-2023 - Pertiwi Puspita Nugraheni; Tri Oldy Rotinsulu; Mauna Th. B. Marais (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the main determinants that influence North Sulawesi's exports to European Union countries in the 2017–2023 period. Using a quantitative approach and panel data analysis, this research identifies the influence of factors such as Gross Domestic Product (GDP) per capita of export destination countries, inflation rates, and currency exchange rates on export performance. The research results show that GDP per capita and inflation have a positive and significant influence on exports, while the exchange rate shows an insignificant negative relationship. The main commodities exported include coconut products, fisheries and spices, with the Netherlands and Germany as the main trading partners. This research recommends product diversification, improving quality, and optimizing infrastructure to strengthen the competitiveness of North Sulawesi export products in the international market.